(untitled) (Philologia, 2021)
The article examines the phenomenon of the Avant-Pop movement from the perspective of its potential as the ﬁrst organised literary movement exceeding the Modern Age speciﬁc setting of Geistesgeschichte paradigms. Focusing upon the nature of Avant-Pop’s avant-gardism and its fundamental attachment to the contemporary electronic media, the study ﬁrst examines the broader social, cultural and economic environment surrounding the emergence of the movement, discusses and deﬁnes the mechanisms at its core, and applies them to those traditional aspects of literature, which provide an insight primarily into the relation between the paradigms of Subject and Transcendence. Examined against the Avant-Pop production employing the traditional literary medium, the established results of such application correspond to the Avant-Pop practice.